Comparison of CMAS corrosion and sintering induced microstructural characteristics of APS thermal barrier coatings. Issue 3 (March 2019) - Wu, Yiyou; Luo, Hua; Cai, Canying; Wang, Yanguo; Zhou, Yichun; Yang, Li; Zhou, Guangwen
Abstract: The microstructural features of high-temperature sintered and CaO-MgO-Al2 O3 -SiO2 (CMAS) corroded air plasma sprayed Y2 O3 stabilized ZrO2 (YSZ) thermal barrier coatings (TBCs) under the thermal gradient condition were comparatively studied. As-sprayed YSZ has a lamellar structure and the lamellae are composed of closely aligned columnar crystals. The sintered and the CMAS corroded YSZ coatings maintain the t'-ZrO2 phase as the as-sprayed YSZ coating. The sintered YSZ remains the lamellar structure with reduced interlamellar gaps and grains coarsening. After the CMAS corrosion, the top layer of the YSZ coating keeps its lamellar structure consisting of some columnar grains with the CMAS infiltration into the intergrain gaps and the formation of striped Zr2 Y2 O7 . The typical lamellar structure transforms into more equiaxed grains in the middle and bottom layers of the ceramic coating along with significant infiltration of amorphous CMAS and anorthite formation in the bottom layer owing to the high contents of Ca and Al.